Dynamical system analysis for a nonminimal torsion-matter coupled gravity - Carloni, Sante; Lobo, Francisco S. N.; Otalora, Giovanni [UNESP]; Saridakis, Emmanuel N. (American Physical Society (APS), 2016)
In this work, we perform a detailed dynamical analysis for the cosmological applications of a nonminimal torsion-matter coupled gravity. Two alternative formalisms are proposed, which enable one to choose between the easier approach for a given problem, and furthermore, we analyze six specific models. In general, we extract fixed points corresponding either to dark-matter-dominated, scaling decelerated solutions, or to dark-energy-dominated accelerated solutions. Additionally, we find that there is a small parameter region in which the model can experience the transition from the matter epoch to the dark-energy era. These features are in agreement with the observed evolution of the Universe, and make the theory a successful candidate for the description of nature.